High prevalence of false-positive plateau phenomena during VO2max testing in adolescents - Beltrami, F. G.; Wong, D. P.; Noakes, T. D. (Journal of Science and Medicine in Sport, 2014)
Objectives: It is believed that a plateau in oxygen consumption (VO2) at the end of an incremental exercise test identifies the upper limits of cardiovascular capacity. We investigated how different criteria influence the frequency with which the plateau phenomenonis detected and the prevalence at which false plateau phenomena occurs during sub-maximal exercise. Design: Cross-sectional. Methods: Six different criteria with 3 different sampling intervals each were used to identify the plateau phenomenon from a single data set comprising 63 incremental exercise tests along with secondary criteria based on target heart rate (HR) and respiratory exchange ratio (RER). A single criterion from the original 18 (HALF) was also used to detect the incidence of any plateau phenomena during each test. Results: The plateau phenomenon was detected in 82% of the tests depending on the criteria used, mostly as a result of the different sampling intervals. HALF identified 103 plateau phenomena but 73 (70.9%) of these occurred during sub-maximal exercise an plateaus were verified by at least one secondary criterion in 27% of cases. Participants reached the HR and RER targets after 83.6 ± 11.7% and 81.9 ± 18.1% of total test duration, respectively. Conclusions: The wide range in the percentage of plateau phenomena detected by different criteria plus the high rate (71%) of false plateau during sub-maximal exercise could indicate that this phenomenon is a calculation artifact rather than an indicator of true physiological events. Secondary criteria can be reached early in exercise and often identify false plateau phenomena as true.